2018
DOI: 10.18510/hssr.2018.6214
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Islamic Gift Economy for Sustainable Development at the Local Level

Abstract: Purpose:The general objective of this study is to explore the potential of Islamic Gift Economy in relation to sustainable development at the local level. This paper is therefore, highlights conceptually some preliminary insights on how the Sustainable Development (SD) and the Islamic Economy can be incorporated into a broader sustainability framework involving the three pillars of economic, social and environmental (ESE) sustainability.Methodology: This paper is abouta preliminary conceptual exploration into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…As mentioned earlier the ISE may pave the way to consider how local populations could reach certain objectives and satisfy certain needs using techniques characteristic of IGE and, thus, carve out a social and economic space of their own to alleviate poverty and improve livelihoods (Salih & Robani, 2018). The researchers observed that the community of MBS Slemanshare a common vision and values towards achieving a common goal.…”
Section: Socio-economic Sustainability Sphere In Mbs Sleman Yogyakartamentioning
confidence: 93%
See 3 more Smart Citations
“…As mentioned earlier the ISE may pave the way to consider how local populations could reach certain objectives and satisfy certain needs using techniques characteristic of IGE and, thus, carve out a social and economic space of their own to alleviate poverty and improve livelihoods (Salih & Robani, 2018). The researchers observed that the community of MBS Slemanshare a common vision and values towards achieving a common goal.…”
Section: Socio-economic Sustainability Sphere In Mbs Sleman Yogyakartamentioning
confidence: 93%
“…In this regard, development should not be viewed solely as economic growth but also concerns for human welfare, community well-being, and social justice. Robani & Salih (2018) highlights that poverty alleviation and improving livelihoods are the core issues of sustainable development at the local level. They assert that from the sustainable development perspective at the community level, economic sustainability must place greater emphasis on boosting economic opportunities and making a profound economic transformation to improve livelihoods and to end extreme poverty.…”
Section: The Ese (Economy-social-environmental) Framework Of Sustainamentioning
confidence: 99%
See 2 more Smart Citations
“…Islamic Social finance (ISF), which includes zakat, infaq , sadaqah , waqf, and Islamic microfinance, is critical to promoting a long-term economic development [ 1 – 3 ]. Islamic social finance has a vital role in solving the problem of poverty [ 3 6 ], income inequality [ 7 ], global education [ 8 , 9 ], health access [ 10 ], and various other socio-economic problems. The role of Islamic social finance instruments is not only in the majority Muslim countries, but also in minority Muslim countries, such as the role of zakat in providing supportive programs for the poor in Singapore [ 11 ], the role of Islamic social finance to support economic resilience in the UK [ 12 ], and the role of zakat in creating prosperity in Germany, France, and Croatia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%